Artists' techniques (Modern at and modernism : Manet to Pollock, 1993)
Examines five paintings: Gleyre's Lost Illusions, Renoir's La Parisienne, Manet's Dejeuner sur l'Herbe, Monet's Autumn at Argenteuil, and Cezanne's Mountains Seen from l'Estaque, for the techniques which each artist employed.